Topotactic reduction as a route to new close-packed anion deficient perovskites: structure and magnetism of 4H-BaMnO(2+x). - Hadermann, J; Abakumov, A; Adkin, J; Hayward, M (2009)
The anion-deficient perovskite 4H-BaMnO(2+x) has been obtained by a topotactic reduction, with LiH, of the hexagonal perovskite 4H-BaMnO(3-x). The crystal structure of 4H-BaMnO(2+x) was solved using electron diffraction and X-ray powder diffraction and further refined using neutron powder diffraction (S.G. Pnma, a = 10.375(2) A, b = 9.466(2) A, c = 11.276(3) A, at 373 K). The orthorhombic superstructure arises from the ordering of oxygen vacancies within a 4H (chch) stacking of close packed c-type BaO(2.5) and h-type BaO(1.5) layers. The ordering of the oxygen vacancies transforms the Mn(2)O(9) units of face-sharing MnO(6) octahedra into Mn(2)O(7) (two corner-sharing tetrahedra) and Mn(2)O(6) (two edge-sharing tetrahedra) groups. The Mn(2)O(7) and Mn(2)O(6) groups are linked by corner-sharing into a three-dimensional framework. The structures of the BaO(2.5) and BaO(1.5) layers are different from those observed previously in anion-deficient perovskites providing a new type of order pattern of oxygen atoms and vacancies in close packed structures. Magnetization measurements and neutron diffraction data reveal 4H-BaMnO(2+x) adopts an antiferromagnetically ordered state below T(N) approximately 350 K.